Pengenalan Perbanyakan Bibit Tanaman Buah Pada Masyarakat - Novalina, Lusi; Fariadi, Herri (Jurnal Gotong Royong, 2024)
The 2023 Dehasen University Bengkulu Community Service Program (KKN) was held at the Department of Food Crops Horticulture and Plantations UPTD BITPHPP in Tabalagan Village, Semidang Lagan District, Central Bengkulu Regency, Bengkulu Province. The work program carried out during this KKN period is "Artificial Vegetative Propagation of Fruit Plant Seedlings". This work program aims to make the community aware of how to propagate fruit plants effectively and efficiently. So that the output that you want to produce from this activity is a scientific article in the Journal of Community Service, a video of activities published on GoogleDrive and a Final Report in the form of a Report on the Results of the Implementation of UNIVED Thematic KKN Bengkulu Period 1 The methods used in Thematic Community Service (KKN) are participation methods, observation, interviews, literature study and documentation.